RIGD: A Database for Intronless Genes in the Rosaceae - Chen, Tianzhe; Meng, Dandan; Liu, Xin; Cheng, Xi; Wang, Han; Jin, Qing; Xu, Xiaoyu; Cao, Yunpeng; Cai, Yongping (Frontiers in Genetics, 2020)
Most eukaryotic genes are interrupted by one or more introns, and only prokaryotic genomes are composed of mainly single-exon genes without introns. Due to the absence of introns, intronless genes in eukaryotes have become important materials for comparative genomics and evolutionary biology. There is currently no cohesive database that collects intronless genes in plants into a single database, although many databases on exons and introns exist. In this study, we constructed the Rosaceae Intronless Genes Database (RIGD), a user-friendly web interface to explore and collect information on intronless genes from different plants. Six Rosaceae species, Pyrus bretschneideri, Pyrus communis, Malus domestica, Prunus persica, Prunus mume and Fragaria vesca, are included in the current release of the RIGD. Sequence data and gene annotation were collected from different databases and integrated. The main purpose of this study is to provide gene sequence data. In addition, attribute analysis, functional annotations, subcellular localization prediction, and GO analysis are reported. The RIGD allows users to browse, search, and download data with ease. Blast and comparative analyses are also provided through this online database, which is available at http://www.rigdb.cn/.